Resposta :
Resposta:
. x = - 5/2
Explicação passo-a-passo:
.
. y = 2x + 3
.
y = - 2 ==> 2x + 3 = - 2
. 2x = - 2 - 3
. 2x = -5
. x = - 5/2
.
(Espero ter colaborado)
Resposta:
y = 2x + 3
x = ?
y = - 2
Resolução:
[tex]\sf \displaystyle y = 2x + 3[/tex]
[tex]\sf \displaystyle - 2 = 2x + 3[/tex]
[tex]\sf \displaystyle 2x + 3 = - 2[/tex]
[tex]\sf \displaystyle 2x = - 2 - 3[/tex]
[tex]\sf \displaystyle 2x = - 5[/tex]
[tex]\boxed{ \boxed { \boldsymbol{ \sf \displaystyle x = -\: \frac{5}{2} } }} \quad \gets \mathbf{ Resposta }[/tex]
Explicação passo-a-passo: